AN ANNOTATED TRANSLATION OF ANY MINUTE - Agus Wibowo (STKIP PGRI Lubuklinggau, 2019)
This research is an annotated translation. The object of the research is an English novel entitled Any Minute. The problems of the research are: 1) What are the difficulties the translator/researcher encountered during the process of translating the novel Any Minute? and 2) What are the solutions for those problems/difficulties? The objectives of this research are: a) to attain factual information concerning the problems/difficulties faced by the researcher and b) to solve the problems/difficulties in the course of translating the source text. In this annotated translation research, the translator/researcher uses the introspective and retrospective methods. The result and analysis reveal that there are 2 words, 8 phrases, 2 clauses, 8 sentences, and 5 idioms from the 25 data of the aspects of languages analyzed that were difficult for the translator/researcher. Those difficulties were at the same time became the problems of the translator/researcher. The solutions of the problems were attained by the annotation or analysis done relevant to the translation strategies and translation theories.